The Use of Preferred Items in a Word-Learning Task: Effects on On-Task Behaviour and Learning Outcomes of Children With Autism Spectrum Disorder. Issue 1 (17th November 2014) - Keen, Deb; Pennell, Donna
Abstract : Identifying and using preferred items and activities to increase motivation and participation of children with autism spectrum disorder (ASD) has been an important and frequently used intervention strategy. Preferred objects, typically identified through a preference assessment, are most frequently used during instruction as reinforcers. These objects may be offered contingent upon a correct response or following a set period of work or may be made available continuously by incorporating them into the learning task. This alternating treatment design study examined the effects of offering preferred items during a word-learning task on learning and on-task behaviour under 2 conditions: following the completion of a set of learning trials ( sequential ) or continuously during a set of learning trials ( embedded ). Participants were 3 children with ASD aged 3–5 years. Results showed that children were more on task when preferred items were embedded, but the sequential condition led to superior learning of target behaviours for 2 of the children. Implications of using preferred items to enhance learning and on-task behaviour are discussed.